Evaluating Occupational Health and Safety Conditions among Security Guards in a Ghanaian Public University (International Journal of Occupational Safety and Health, 2025)
Introduction: The occupational health and safety (OHS) issues at academic institutions have received little attention, especially regarding the security staff who face specific job-related risks. This paper examines the safety climate, risk exposures, and occupational health and safety (OHS) policies among security guards at the University of Cape Coast, Ghana.Methods: A cross-sectional study was conducted from July to October 2023, employing both quantitative and qualitative approaches. Structured questionnaires, including the validated NOSACQ-50 tool, observational checklists, and expert-led risk assessments, were used in data collecting. The study comprised 162 security guards with a minimum of one year of experience. The relationship between knowledge, attitudes, and safety outcomes was evaluated using descriptive statistics, chi-square tests, and correlation analyses. Results: With a mean score of 2.25 ± 0.17, the general safety climate was judged to be poor; management's safety commitment and communication received especially low ratings. Among the main occupational hazards were psychological risks (67.8%), environmental exposures (76.2%), and ergonomic stresses (87.7%). Among the frequently mentioned health issues were occupational stress (86.4%) and low back pain (74.0%). Only 23.5% of participants regularly reported exposures; hence, reporting of occupational injuries was less than ideal. High-risk areas identified by risk assessments as needing immediate mitigation included musculoskeletal injuries, stress, and insect bites. Conclusion: Overall, the report exposes notable shortcomings in the OHS infrastructure and security environment for Ghanaian university staff. To ensure a safer workplace for security personnel, effective training, managerial commitment, policy implementation, and risk-reduction techniques are urgently needed.